The Long Non-coding RNA TMPO-AS1 Promotes Bladder Cancer Growth and Progression via OTUB1-Induced E2F1 Deubiquitination - Zhang, Yeyu; Zhu, Yuxing; Xiao, Mengqing; Cheng, Yaxin; He, Dong; Liu, Jianye; Xiang, Liang; Gong, Lian; Wang, Zhanwang; Deng, Liping; Cao, Ke (Frontiers in Oncology, 2021)
Background Increasing evidence indicates long non-coding RNAs (lncRNAs) play crucial roles in cancer tumorigenesis and progression. TMPO antisense RNA 1 (TMPO-AS1) has been found to be involved in several cancers by acting as an competing endogenous RNA. However, the potential roles of TMPO-AS1 interacting with proteins in bladder cancer (BC) remain poorly understood. Methods The lncRNA TMPO-AS1 expression was evaluated by bioinformatics analysis and further validated by qRT-PCR. Loss- and gain-of- function assays were performed to determine the biological functions of TMPO-AS1 in BC proliferation, migration, and invasion. Chromatin immunoprecipitation, luciferase reporter assays, western blotting, RNA pull-down, RNA immunoprecipitation assays, and fluorescence in situ hybridization were conducted to explore the upstream and downstream molecular mechanisms of TMPO-AS1. Results TMPO-AS1 is upregulated in bladder cancer. Functional experiments demonstrated that TMPO-AS1 promotes bladder cancer cell proliferation, migration, invasion, and inhibits cell apoptosis in vivo and in vitro. Mechanically, E2F1 is responsible for the TMPO-AS1 upregulation. Additionally, TMPO-AS1 facilitates the interaction of E2F1 with OTU domain-containing ubiquitin aldehyde binding 1 (OTUB1), leading to E2F1 deubiquitination and stabilization, thereby promotes BC malignant phenotypes. Furthermore, rescue experiments showed that TMPO-AS1 promotes BC growth in an E2F1-dependent manner. Conclusions Our study is the first to uncover a novel positive regulatory loop of TMPO-AS1/E2F1 important for the promotion of BC malignant behaviors. The TMPO-AS1/E2F1 loop should be considered in the quest for new BC therapeutic options.